Anal Intercourse Among Female Sex Workers in Côte d'Ivoire: Prevalence, Determinants, and Model-Based Estimates of the Population-Level Impact on HIV Transmission. Issue 2 (14th June 2017) - Maheu-Giroux, Mathieu; Baral, Stefan; Vesga, Juan F; Diouf, Daouda; Diabaté, Souleymane; Alary, Michel; Abo, Kouamé; Boily, Marie-Claude
Abstract: Current evidence suggests that anal intercourse (AI) during sex work is common in sub-Saharan Africa, but there have been few studies in which the contribution of heterosexual AI to human immunodeficiency virus (HIV) epidemics has been investigated. Using a respondent-driven sampling survey of female sex workers (FSWs; n = 466) in Abidjan, Côte d'Ivoire, in 2014, we estimated AI prevalence and frequency. Poisson regressions were used to identify AI determinants. Approximately 20% of FSWs engaged in AI during a normal week (95% confidence interval: 15, 26). Women who performed AI were generally younger, had been selling sex for longer, were born in Côte d'Ivoire, and reported higher sex-work income, more frequent sex in public places, and violence from clients than women not reporting AI. Condom use was lower, condom breakage/slippage more frequent, and use of water-based lubricants was less frequently reported for AI than for vaginal intercourse. Using a dynamic transmission model, we estimated that 22% (95% credible interval: 11, 37% of new HIV infections could have been averted among FSWs during 2000–2015 if AI had been substituted for vaginal intercourse. Despite representing a small fraction of all sex acts, AI is an underestimated source of HIV transmission. Increasing availability and uptake of condoms, lubricants, and pre-exposure prophylaxis for women engaging in AI could help mitigate HIV risk.